Relatıonshıp between sıck buıldıng syndrome and ındoor aır qualıty among hospıtal staff - Arikan, Inci; Tekin, Ömer Faruk; Erbas, Oğuzhan (La Medicina del Lavoro, 2018)
Background: Sick building syndrome (SBS) is defined as a condition occurring in those who live or work in a modern building and who suffer from symptoms such as headache, fatigue, lack of concentration and irritation of the skin and mucous membranes. Objectives: The aim of this study was to evaluate the relationship between personal characteristics, environmental factors and the prevalence of SBS among the secretaries working in a hospital. Method: In this cross-sectional study, questionnaires were administered to all secretaries who were working in Kütahya hospital in January and March 2018. The questionnaire used in the study included the sociodemographic characteristics of the participants and the question form “MM 040 NA Hospital” to evaluate SBS symptoms. These symptoms were the clinical symptoms reported by the secretaries as a result of exposure to factors within the hospital. Temperature, humidity, carbon dioxide concentration, light intensity and noise level were measured in the indoor environment of the hospital. Chi square test, Spearman’s correlation coefficient and logistic regression models were used in the analysis of data. Results: The study was completed with 177 people, 61.6% women, and the mean age was 30.14±5.7. The prevalence of SBS was found to be 20.9%. The risk of SBS was found to be 2.9 times higher for females, 2.8 times higher for individuals who described the working environment as dusty, 2.6 times higher for subjects complaining of stuffy “bad” air, dry air and an unpleasant odour. All measurements were found to be within acceptable limits. The risk of SBS was found to be 1.2 times higher with increases in the measured noise level, and 2.1 times higher with increased carbon dioxide (CO2) concentrations. Conclusion: The factors impacting the risk of experiencing SBS were determined. Bearing these factors in mind, we think that hospital administrations should be informed about arrangements and measures that will improve the quality of the internal environment of the hospital.